Description of the larval instars of Gonatopus bartletti Olmi, 1984 (Hymenoptera: Dryinidae) - Guglielmino, A.; Bückle, C.; Moya-Raygoza, G. (Zootaxa, 2006)
The postembryonic development and external morphology of each larval instar of Gonatopus bartletti Olmi, 1984 are described and illustrated. The affinities among the immature and mature larvae of G. bartletti and corresponding instars of other species of the same subfamily are discussed. The mature larva shows a peculiar structure never observed in other Gonatopodinae species; near the base of each mandible is a peculiar subrectangular heavily sclerotized and dark pigmented area with a lens-shaped transparent protuberance in its anterolateral angle. Its function is unknown.